2016
DOI: 10.31403/rpgo.v62i1897
|View full text |Cite
|
Sign up to set email alerts
|

Anomalías cromosómicas en abortos espontáneos

Abstract: Introducción: El 15 a 20% de las gestaciones clínicas terminan en aborto espontáneo y 25% de las mujeres sufrirán un aborto a lo largo de su vida. En más del 50% de los casos de abortos espontáneos se puede identificar una o más anomalías cromosómicas. Objetivos: Determinar la frecuencia de anomalías cromosómicas en restos de abortos espontáneos y su relación con edad materna y otros parámetros como la edad gestacional. Diseño: Estudio de tipo observacional, descriptivo, transversal sobre base de datos secunda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 21 publications
0
3
0
5
Order By: Relevance
“…44 Chromosomal abnormalities represent one of the main causes of pregnancy loss, requiring a karyotype analysis in couples. These changes were found in 9.3% of the cases with predominance of mosaicism, 2 68.8% with predominance of autosomal trisomy, 4 and 55.4% with predominance of trisomy of chromosome 16. 45 Venous and cardiovascular disorders can be associated with spontaneous abortion.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…44 Chromosomal abnormalities represent one of the main causes of pregnancy loss, requiring a karyotype analysis in couples. These changes were found in 9.3% of the cases with predominance of mosaicism, 2 68.8% with predominance of autosomal trisomy, 4 and 55.4% with predominance of trisomy of chromosome 16. 45 Venous and cardiovascular disorders can be associated with spontaneous abortion.…”
Section: Discussionmentioning
confidence: 95%
“…[1][2][3] This problem is defined as the involuntary termination of pregnancy, up to 20-22 gestational weeks. 4 Its recurrent form is characterized by the loss of three or more pregnancies, consecutively. 2 Of all diagnosed pregnancies, 15 to 20% end in spontaneous abortion, most within the first 13 weeks of pregnancy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, to a lesser extent, fetuses with anomalies such as Down syndrome, Patau, Edwards, Wolf, Potter, Di George, Robinow, Treacher-Collins syndrome, or intersex anomalies were observed. -Alferez et al, (2016) in a study on abortive human fetuses and chromosomal malformations, indicated that the most frequent chromosomal anomalies in spontaneously aborted fetuses were trisomies 16, 22 and 9. These are anomalies mostly in internal organs and without clear distinctive macroscopic features.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, they probably correspond to fetuses that have been classified as hypertelorism and micrognathia without a clear syndromic correspondence. In addition, these malformations have been determined in fetuses older than six months, so it would be very likely to find younger fetuses with the chromosomal alterations described by Mora-Alferez et al, (2016).…”
Section: Discussionmentioning
confidence: 99%